2015
DOI: 10.1118/1.4933197
|View full text |Cite
|
Sign up to set email alerts
|

Technical Note: Phantom study to evaluate the dose and image quality effects of a computed tomography organ‐based tube current modulation technique

Abstract: Purpose: This technical note quantifies the dose and image quality performance of a clinically available organ-dose-based tube current modulation (ODM) technique, using experimental and simulation phantom studies. The investigated ODM implementation reduces the tube current for the anterior source positions, without increasing current for posterior positions, although such an approach was also evaluated for comparison. Methods: Axial CT scans at 120 kV were performed on head and chest phantoms on an ODM-equipp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 25 publications
1
24
0
Order By: Relevance
“…Herein, we gave an overview of the dose-reducing potential of OBTCM reported in the literature. All studies were performed with anthropomorphic phantoms in which the breasts were centered anteriorly and fully located in the reduced current zone (7,(9)(10)(11)(12). The real position of the breasts in women lying supine is more lateral, which explains the lower potential for breast dose reduction observed in our study.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Herein, we gave an overview of the dose-reducing potential of OBTCM reported in the literature. All studies were performed with anthropomorphic phantoms in which the breasts were centered anteriorly and fully located in the reduced current zone (7,(9)(10)(11)(12). The real position of the breasts in women lying supine is more lateral, which explains the lower potential for breast dose reduction observed in our study.…”
Section: Discussionmentioning
confidence: 91%
“…Dose reduction to the female breast with use of OBTCM and the resulting effect on posterior organs have been investigated before with anthropomorphic phantoms (6,7,9,10,11). Duan et al (6) indicated an increase in posterior surface dose, suggesting a possible higher lung dose, whereas Wang et al (10) reported an elevated dose to the spine and lungs.…”
Section: Discussionmentioning
confidence: 99%
“…Monte Carlo simulations, which stochastically model the transport of photons, are typically used to estimate the distribution of radiation dose deposited in an object. Dose deposition maps and organ doses estimated via Monte Carlo simulations have been widely used to quantify radiation dose, [13][14][15][16][17] evaluate CT dose reduction techniques, [18][19][20][21] and to optimize CT scan parameters. 22,23 Monte Carlo simulations are traditionally slow, though recent advancements in acceleration and GPU implementation have greatly reduced run times.…”
Section: Introductionmentioning
confidence: 99%
“…In a second approach, implemented by GE Medical Systems with ODM, mA is reduced when the x-ray tube rotates over the anterior part of the patient's body without increase over the remaining lateral and posterior parts. However, this approach has been documented to deliver images of increased noise [10,11]. Previous studies performed in adult patients have shown that OTCM may substantially reduce radiation dose to superficial radiosensitive organs [6,8,12,13].…”
Section: Introductionmentioning
confidence: 99%